경도인지장애 고령자의 우울과 인지기능 및 삶의 질에 대한 숲 체험 중재 프로그램의 효과 - 전아영(Ah Young Jun); 이강숙(Kang-Sook Lee); 이선미(Sun-Mi Lee) (보건교육건강증진학회지, 2019)
Objectives: The purpose of this study was to investigate the effects of depression and cognitive function on the quality of life of elderly people diagnosed with mild cognitive impairment through various forest experience intervention program. Methods: The general characteristics of the tests subjects were verified by frequency and percentage, Fisher 's exact test, χ² test, and a t–test was conducted to verify the pre-and post- effects of the forest experience intervention program. Results: The results of this study showed that there was no significant difference in cognitive function between experiment group and control group experiencing forest experience intervention program, but it was statistically proved that depression of experimental group decreased and quality of life improved(p<.05). Conclusions: The study tried to present a new dementia prevention program that was different from the existing cognitive enhancement program method. KCI Citation Count: 0